Effect of Source–Drain Electric Field on Charge Transport Mechanism in Polymer‐Based Thin‐Film Transistors. Issue 16 (9th March 2021) - Biswas, Swarup; Seo, Kyeong-Ho; Lee, Yongju; Kim, Yun-Hi; Bae, Jin-Hyuk; Kim, Hyeok
Abstract : Donor–acceptor copolymer‐based field‐effect transistors (FETs) have attracted considerable attention from technological and academic perspectives due to their low band gap, high mobility, low cost, and easy solution processability, flexibility, and stretch ability. Among different solution‐processing techniques, meniscus‐guided coating has the potential for large‐area film formation. Moreover, 29‐diketopyrrolopyrroleselenophene vinylene selenophene (29‐DPP‐SVS) donor‐acceptor copolymer‐based FETs have already exhibited excellent performance due to their short π–π stacking distance and strong π–π interaction. Charge carrier mobility of these types of semiconducting materials is significantly dependent on the applied electric field. Therefore, detailed analysis of the electric‐field dependency of charge carrier mobility is necessary to understand the transport mechanisms within these materials. Thus, herein, 29‐DPP‐SVS‐based FETs are fabricated by varying the blade‐coating speed of their semiconductor layer. Then, the effect of the blade‐coating speed on the electrical properties of the FETs is studied through the analysis of electric‐field‐dependent mobility. The results suggest that the charge carrier mobility of different FETs is dependent on the applied electric field and that the type of dependency is Poole–Frenkel. At an optimized blade‐coating speed (2 mm s −1 ), the device exhibits maximum zero‐field mobility (3.39 cm 2  V −1  s −1 ) due to the low trap density within the conducting channel. Abstract : Herein, the effect of the blade‐coating (BC) speed on the charge transport mechanism is investigated within the organic FETs (29‐DPP‐SVS based) through a detailed analysis of their electric‐field‐dependent mobility. The results demonstrate that the carrier mobility values of different FETs are dependent on the applied electric field and BC speed. At 2 mm s −1 BC speed (optimized), the device exhibits maximum zero‐field mobility (3.39 cm 2  V −1  s −1 ) due to the low trap density within the conducting channel.